Defining Islamic Statehood - Abdul Rauf, Imam Feisal. author. aut Link
XVI, 318 p.
Keywords: This groundbreaking book offers in-depth analysis of the modern Islamic state, applying a quantitative measurement of how Muslim majority nations meet the definition. Content for the book was developed through extensive debate among a panel of distinguished Sunni and Shia Muslim scholars over seven years.